Synthesis and characterization of poly(N-vinylcaprolactam)-based spray-dried microparticles exhibiting temperature and pH-sensitive properties for controlled release of ketoprofen. (2nd September 2017) - Medeiros, Simone F.; Lopes, Milene V.; Rossi-Bergmann, Bartira; Ré, Maria Inês; Santos, Amilton M.
Abstract: Poly( N -vinylcaprolactam) (PNVCL) and poly( N -vinylcaprolactam- co -acrylic acid) (poly(NVCL- co- AA)) were synthesized by solution-free radical polymerization and displayed thermo-responsive behavior, with lower critical solution temperatures (LCSTs) of 35 °C and 39 °C, respectively. The incorporation of AA unities made the poly(NVCL- co -AA) sensitive to both pH and temperature. They were exploited in this work in preparing microparticles loaded with ketoprofen via spray-drying to modulate the drug release rate by changing pH or temperature. The interaction between polymer and drug was studied using X-ray diffractometry, Raman spectrometry and scanning electron microscopy (SEM). The biocompatibility of pure polymers, free ketoprofen as well as the spray-dried particles was demonstrated in vitro by low cytotoxicity and a lack of nitric oxide production in macrophages at concentrations as high as 100 µg/ml. The release profile of ketoprofen was evaluated by in vitro assays at different temperatures and pH values. Drug diffusion out of PNVCL's hydrated polymer network is increased at temperatures below the LCST. However, when poly(NVCL- co -AA) was used as the matrix, the release of ketoprofen was primarily controlled by the pH of the medium. These results indicated that PNVCL and the novel poly(NVCL- co -AA) could be promising candidates for pH and temperature-responsive drug delivery systems.